2009
DOI: 10.4236/jemaa.2009.14040
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Computation of Resonant Frequency of Shorting Post Loaded Gap-Coupled Circular Microstrip Patch Antennas

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The simulation is performed by using the Method of Moment based commercially available simulator IE3D. In [23], an expression for the resonant frequency of two gapcoupled circular microstrip patch antennas loaded with shorting post is derived by using the similar approach as in [22]. It is shown that such combination leads to a very accurate model of the two gap-coupled circular microstrip antennas loaded with shorting post.…”
Section: Numerical Modelling Of Gap-coupled Microstrip Antennasmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation is performed by using the Method of Moment based commercially available simulator IE3D. In [23], an expression for the resonant frequency of two gapcoupled circular microstrip patch antennas loaded with shorting post is derived by using the similar approach as in [22]. It is shown that such combination leads to a very accurate model of the two gap-coupled circular microstrip antennas loaded with shorting post.…”
Section: Numerical Modelling Of Gap-coupled Microstrip Antennasmentioning
confidence: 99%
“…The gap between the two patches at the point of coupling can be considered as a π-type network [22,23]. It is shown in Fig.…”
Section: Numerical Modelling Of Gap-coupled Microstrip Antennasmentioning
confidence: 99%
“…Increase of the bandwidth of this type of the antenna, in general, requires reducing the substrate permittivity or increasing its thickness, since the exact shape of the patch does not have a dominant effect on the bandwidth if the overall dimensions are similar. Using the gap-coupled resonators, the bandwidth of the microstrip antennas can be increased [2][3][4][5]. Recently, researchers have presented a bandwidth enhancement method for low profile E-shaped microstrip patch antennas in [6].…”
mentioning
confidence: 99%